2019
DOI: 10.1177/1078390319846548
|View full text |Cite
|
Sign up to set email alerts
|

Spiritual Perspectives, Spiritual Care, and Knowledge of Recovery Among Psychiatric Mental Health Nurses

Abstract: BACKGROUND: Promoting spiritual well-being aids the mental health recovery process. Furthermore, nursing governance bodies and national mental health care regulators support spiritual care as a mental health–promoting approach. Although spiritual well-being is integral to quality of life in people with mental illness, little is known about the psychiatric mental health (PMH) nurses’ provision of spiritual care. AIMS: Spiritual perspectives, frequency of spiritual care, and knowledge of recovery-orient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 44 publications
1
11
0
2
Order By: Relevance
“…2015; Klockmo 2013; Marshall et al . 2013; Meehan & Glover 2009; Mugnier 2017; Neathery 2018; Ofina 2016; Peebles et al . 2009; Repique et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2015; Klockmo 2013; Marshall et al . 2013; Meehan & Glover 2009; Mugnier 2017; Neathery 2018; Ofina 2016; Peebles et al . 2009; Repique et al .…”
Section: Resultsmentioning
confidence: 99%
“…2015; Hungerford et al . 2015; Klockmo 2013; Meehan & Glover 2009; Mugnier 2017; Neathery 2018; Repique et al . 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, a study by (Neathery et al, 2020) also reported that spirituality helped patients with mental disorders live well. It increased hope, self-esteem, well-being, satisfaction with care, and social support.…”
Section: Nurses' Experiences Of Providing Spiritual Interventionsmentioning
confidence: 96%
“…After critiquing eight existing tools for quantifying nurses' spiritual care attitudes and provision, Garssen et al (2016) in another study (Neathery et al, 2019) and 382 nurses enrolled in a post-licensure program at a public university in the "Bible Belt" (Green et al, 2019) also were observed to have higher scores on the NSCTS. Findings from these US studies indicated nurses reported on average providing each of the 17 therapeutics between 1-2 times and 3-6 times during the previous 72-80 h of providing patient care, with total sum scores above 40.…”
Section: Backg Rou N Dmentioning
confidence: 99%